Identification of an endoplasmic reticulum proteostasis modulator that enhances insulin production in pancreatic β cells. Issue 6 (16th June 2022) - Miyake, Masato; Sobajima, Mitsuaki; Kurahashi, Kiyoe; Shigenaga, Akira; Denda, Masaya; Otaka, Akira; Saio, Tomohide; Sakane, Naoki; Kosako, Hidetaka; Oyadomari, Seiichi
Summary: Perturbation of endoplasmic reticulum (ER) proteostasis is associated with impairment of cellular function in diverse diseases, especially the function of pancreatic β cells in type 2 diabetes. Restoration of ER proteostasis by small molecules shows therapeutic promise for type 2 diabetes. Here, using cell-based screening, we report identification of a chemical chaperone-like small molecule, KM04794, that alleviates ER stress. KM04794 prevented protein aggregation and cell death caused by ER stressors and a mutant insulin protein. We also found that this compound increased intracellular and secreted insulin levels in pancreatic β cells. Chemical biology and biochemical approaches revealed that the compound accumulated in the ER and interacted directly with the ER molecular chaperone BiP. Our data show that this corrector of ER proteostasis can enhance insulin storage and pancreatic β cell function. Graphical abstract: Highlights: Cell-based screening of UPR signaling identifies that KM04794 inhibits the UPR KM04794 alleviates ER stress and protein aggregation Intracellular insulin levels and insulin secretion are improved by KM04794 Chemoproteomic analysis identifies BiP as a candidate target of KM04794 Abstract : Miyake et al. identify a small molecule, KM04794, that improves ER proteostasis disrupted by ER stress and leads to an increase in insulin secretion. Chemoproteomics analysis reveals accumulation in the ER and shows BiP to be a candidate target of KM04794.